The Impact of Effective Communication on Employee Performance - Sri Windayanti; Fadilla Nurfi Azzahrin; Nur Afni Oktavianisa (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Effective communication has an important role in improving employee performance in the work environment. This study aims to analyze the impact of effective communication on employee performance. The method used is the literature method. Through the literature review method, this study collects and analyzes relevant information regarding the relationship between effective communication and employee performance. The results of the literature analysis revealed that effective communication has a positive impact on employee performance. Good communication affects productivity, improves work quality, and strengthens employee job satisfaction. The results of this study provide an in-depth insight into how effective communication can affect employee performance. The practical implication of this study is the importance of developing effective communication strategies in an organization to improve overall employee performance such as improving communication skills, facilitating clear and open information flow, and encouraging a positive communication culture in the workplace.